Illegitimacy Moderates the Effects of Power on Approach - Lammers, Joris; Galinsky, Adam D.; Gordijn, Ernestine H.; Otten, Sabine (Psychological Science, 2008)
A wealth of research has found that power leads to behavioral approach and action. Four experiments demonstrate that this link between power and approach is broken when the power relationship is illegitimate. When power was primed to be legitimate or when power positions were assigned legitimately, the powerful demonstrated more approach than the powerless. However, when power was experienced as illegitimate, the powerless displayed as much approach as, or even more approach than, the powerful. This moderating effect of legitimacy occurred regardless of whether power and legitimacy were manipulated through experiential primes, semantic primes, or role manipulations. It held true for behavioral approach (Experiment 1) and two effects associated with it: the propensity to negotiate (Experiment 2) and risk preferences (Experiments 3 and 4). These findings demonstrate that how power is conceptualized, acquired, and wielded determines its psychological consequences and add insight into not only when but also why power leads to approach.